PENGARUH LITERASI KEUANGAN DAN TEKNOLOGI DIGITAL TERHADAP KEPUTUSAN INVESTASI SAHAM GENERASI MILENIAL - Ari Yuli Musthofa; Ahmad Husin; Agus Triatmono (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the influence of financial literacy and digital technology partially and simultaneously on stock investment decisions among millennials. The research is conducted against the backdrop of the surge in young retail investors driven by digital accessibility, despite the ongoing challenges of financial literacy levels. The research method employs a quantitative approach with a case study on customers of PT. Mirae Asset Sekuritas in Surakarta. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The independent variables include Financial Literacy and Digital Technology (measured through perceived usefulness and ease of use), while the dependent variable is Stock Investment Decision. The results indicate that: (1) Financial literacy has a positive and significant effect on stock investment decisions, as better understanding helps investors perform rational evaluations and manage risks; (2) Digital technology has a positive and significant effect on stock investment decisions, particularly through ease of real-time information access and analytical features on the platform; (3) Simultaneously, financial literacy and digital technology significantly influence stock investment decisions with an R-Square value ($R^2$) of 0.874. This suggests that 87.4% of the variation in millennial investment decisions can be explained by these two variables, while the remainder is influenced by other factors outside the model Keywords : Financial Literacy, Digital Technology, Investment Decision, Stock, Millennials, Mirae Asset Sekuritas.